Report on Effect of Several Light Truck Defenders in Indian Subcontinent - KHARE, JASMIN (The journal of contemporary issues in business and government, 2021)
The exterior design of the vehicle and other internal components, such as the deflector attached to it, play a major role in aerodynamics. It has been noted that large numbers of light trucks without any aerodynamic features are produced and operated in the Indian subcontinent. The primary objective of this study is therefore to analyze the impact of aerodynamic devices or rails in Bangladesh and Pakistan on light-duty trucks. The study consisted of computer modeling, quick physical models manufacture and wind tunnel testing including CFD analysis. Nonetheless, in the Indian subcontinent, particularly in Bangladesh, India and Pakistan, there are as yet a critical number of light trucks that are operational that is made by changing a Bedford J arrangement truck Analyzed and compared the drag forces produced by each model. The results show that aerodynamically efficient deflectors for most locally produced Bangladeshi and Pakistani trucks can improve the overall aerodynamic drag by up to 22 per cent. The aerodynamic fitting can reduce fuel consumption by 12 percent by replacing these deflectors.